Adsorção e precipitação de ácido aminofosfônico em rocha testemunho e minerais característicos - Bezerra, Bruna Tarciana Cavalcante (2015)
The movement of fluids present in the well moving to surface is caused mainly by the injection of sea water in these petroleum units producing. However, this process induce to scale formation, since the mixing of saline water with the water present in the well leads to formation of insoluble salts. In order to reduce the damage caused by the deposition of these salts employs the squeeze technique of scale inhibitor injection, from which occurs the retention of an anti-fouling on the surface of rock formation by inhibiting the formation of crystals. The present work had as main objective to understand the mechanism of retention of an inhibitor in a characteristic rock of the pre-salt. Therefore, fundamental studies of batch were performed employing a witness rock calcite disaggregated (IL), the main minerals that occur in the formations (calcite and quartz) and as scale inhibitor, the nitrilotrismetylenephosphonic acid (NTMP). It was raised isotherm adsorption/desorption of N2 and XRD characterization of materials used for retention of the inhibitor. The batch experiments were conducted under different operating conditions in a thermostatic bath. Evaluated the influence of temperature, the presence of a surfactant, particle size, addition of cations Ca2+ and Mg2+ and contact time. The inhibitor concentration was determined by analyzing of the amount of phosphorus in solution employing the technique Optical Emission Spectroscopy Inductively Coupled Plasma (ICP-OES). The results led us to conclude that the retention of NTMP in the rock record is controlled by the precipitation of inhibitor; increasing the temperature results in a gradual increase in the amount of trapped inhibitor and the addition of the surfactant Igepal does not cause abrupt variations this retention